Appropriate utilisation of emergency upper gastrointestinal endoscopy in a tertiary referral centre - Alif Gul, Yunus Gul; Jabar, Mohd Faisal; Mo'min, N.; Hon, Sook Kit (Malaysian Medical Association, 2004)
A retrospective cross-sectional study was carried out in a tertiary referral centre to determine the appropriateness of usage of emergency upper gastrointestinal endoscopy (EUGIE) with reference to the guidelines set by the American Society of Gastrointestinal Endoscopy (ASGE). EUGIE was defined as early, non-elective endoscopy performed for in-patients within 48 hours of acute hospital admission. The median age of the 668 patients was 55 years (age range 12- 90), 31% of whom had a previous upper gastrointestinal endoscopy. Bleeding in the form of haematemesis, melaena or anaemia was the most common indication (40.7%) for EUGIE. Eighty one percent of the procedures were judged appropriate by the ASGE guidelines. There was a statistically significant relationship between appropriateness and significant diagnostic yield (P<0.05). Procedures performed for melaena, symptomatic anaemia and haemetemesis led to greater significant diagnostic yield (P<0.05) and there was no difference in the yield between working-hours and after-hours EUGIE.